Disparities in Prevalence of Smoking and Smoking Cessation during Pregnancy: A Population-Based Study. (14th May 2015) - Dias-Damé, Josiane L.; Cesar, Juraci A.
Abstract : Objective . To examine time trends in prevalence of smoking and smoking cessation during pregnancy by family income, maternal level of education, skin color, and age. Methods . We conducted three population-based surveys in 2007, 2010, and 2013 with newly delivered mothers living in the municipality of Rio Grande, Southern Brazil. Data were collected using questionnaires administered after delivery in all (two) maternity units in the city, at Dr. Miguel Riet Corrêa Júnior Hospital and at Santa Casa de Misericórdia. Time trends were analyzed using chi-square test for linear trend. Results . Data of 7, 572 women showed that the prevalence of smoking before pregnancy decreased from 28% (26.2–29.7) in 2007 to 22% (20.8–24.0) in 2013 (P < 0.001 ). Prevalence of smoking during pregnancy decreased from 22% (20.4–23.7) in 2007 to 18% (16.6–19.5) in 2013 (P < 0.001 ). This reduction varied across income ranging from 17% (poorest) to 35% (richest) (P < 0.001 ). The lower the income, the higher the smoking prevalence during pregnancy. Smoking cessation was more prevalent among women of higher level of education and income. Conclusions . Smoking before and during pregnancy is still highly prevalent and the prevalence of cessation is low pointing to a need to strengthen actions targeting low-income, less educated, black pregnant women.